The Effect of Mandatory Disclosure on Market Inefficiencies: Evidence from FASB Statement No. 161 - Campbell, John L.; Khan, Urooj; Pierce, Spencer (The Accounting Review, 2021)
ABSTRACT Prior research finds that unrealized gains/losses on cash flow hedges are negatively associated with future earnings, and that investors and analysts fail to anticipate this association. These studies speculate that this mispricing is due to either poor derivatives disclosures or the accounting model for cash flow hedges. We examine whether enhanced mandatory derivatives disclosures set forth in FAS 161 improve users' understanding of firms' hedging activities and offer three main findings. First, we find that this mispricing does not persist after FAS 161. Second, we find that the correction of mispricing is greatest when disclosure might help investors most. Finally, we find that analyst forecast accuracy improves after FAS 161. Overall, our results suggest that the enhanced mandatory derivative disclosures required by FAS 161 improved users' understanding of the effects of derivative and hedging activities on future firm performance and firm value—and consequently mitigated investor mispricing.